2016
DOI: 10.1080/02770903.2016.1206563
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with generic health-related quality of life in adult asthma patients in Germany: Cross-sectional study

Abstract: Focusing on disease control and screening for depression and anxiety may be promising approaches to improve HRQOL in adult asthma patients. If a patient shows alarming symptoms of anxiety and/or depression, the patient should then be referred for psychiatric treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 40 publications
7
21
0
Order By: Relevance
“…Income, physical activity status, smoking status, coexisting diseases, and depression were associated with impaired HRQoL in all four dimensions: fair/ poor self-rated health, frequent mentally unhealthy days, frequent physically unhealthy days, and frequent days of activity limitation. These results follow other published results that multiple risk factors are associated with impaired HRQoL, including physical inactivity [16], smoking [16], comorbidities [10,18], and depression [12].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Income, physical activity status, smoking status, coexisting diseases, and depression were associated with impaired HRQoL in all four dimensions: fair/ poor self-rated health, frequent mentally unhealthy days, frequent physically unhealthy days, and frequent days of activity limitation. These results follow other published results that multiple risk factors are associated with impaired HRQoL, including physical inactivity [16], smoking [16], comorbidities [10,18], and depression [12].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings indicate that females had significantly higher fair/poor self-rated health than males before adjustment with confounding factors (sex, race/ethnicity, age, income, health care coverage, physical activity, smoking, BMI, coexisting diseases, and depression) included in this study, but was significantly lower after adjustment. Similar to other studies [12,24], this suggests the importance of the effects of the confounding factors on the association between being a female and having fair/poor health. Böhmer, et al found that the association between the mental health score of the Short Form 12 Health Survey Questionnaire and being a female adult with asthma was not significant, after adjusting for confounding factors [12].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This study used baseline data from a longitudinal patient cohort study [ 17 ]. Ethical approval was obtained from the Ethics committee of the University of Regensburg (File-Numbers 12-101-0162, 13-101-0091).…”
Section: Methodsmentioning
confidence: 99%